Rho‐Kinase inhibitor fasudil suppresses high glucose‐induced H9c2 cell apoptosis through activation of autophagy. Issue 5 (October 2016) - Gao, Huikuan; Hou, Fei; Dong, Ruiqing; Wang, Zefeng; Zhao, Can; Tang, Wurina; Wu, Yongquan
Summary: Introduction: Cardiac cell apoptosis plays a crucial role in the progression of diabetic cardiomyopathy. Recent studies have shown that fasudil, a Rho‐kinase (ROCK) inhibitor, inhibits cardiac cell apoptosis; however, the underlying mechanism remains unclear. Aim: This study aimed to investigate whether fasudil protects H9c2 cells from high glucose‐induced apoptosis via activation of autophagy. Methods: Rat cardiomyocyte H9c2 cells were treated with high glucose and used as a diabetic cardiomyopathy model. Cell survival rate, apoptosis, and subcellular morphology were examined using the MTT assay, flow cytometry, and electron microscopy, respectively. ROCK1 and ROCK2 mRNA levels were determined using quantitative real‐time PCR. Bcl‐2 and Bax, myosin phosphatase target subunit‐1 (MYPT‐1), phosphorylated (p)‐MYPT1, LC3‐II/LC3‐I, Beclin‐1, soluble and insoluble P62 protein levels were determined by Western blot analysis. Results: Fasudil reversed the high glucose‐induced inhibition of cell proliferation and suppressed high glucose‐induced early apoptosis. Fasudil also reversed the high glucose‐suppressed Bcl‐2 levels and decreased the high glucose‐induced Bax levels. Further, Fasudil suppressed ROCK levels, expression, promoted autophagy via increasing the LC3‐II/LC3‐I ratio, Beclin‐1 expression, and the number of autophagosomes in H9c2 cells treated with high glucose. These effects of fasudil were abrogated by 3‐methyladenine (3‐MA), an autophagy inhibitor. Conclusion: Fasudil inhibited high glucose‐induced apoptosis in rat H9c2 cells through activating autophagy.